Fixed bed adsorption dynamics of CO2/CH4 mixtures in zeolite 13X for biogas upgrading - Silva, José A.C. (2017)
The separation performance of CO2/CH4 mixtures in binderless beads of zeolite 13X has been studied in a fixed bed adsorption system for biogas upgrading strategies to bio-methane. Zeolite 13X proved to be very efficient for the separation leading to breakthrough curves that show a plateau of pure CH4 of approximately 4 minutes depending of the operating conditions chosen. The separation performance for CO2/CH4 measured by the selectivities range from 37 at a low pressure of 0.1 MPa to approximately 5.0 at the high temperature of 423 K. A mathematical model for fixed bed adsorption studies was used and validated through the experimental data predicting with good accuracy the behavior of the transient breakthrough experiments being a valuable tool for the analysis and design of cyclic adsorption processes (PSA) for biogas upgrading strategies to biomethane and CO2 capture using 13X zeolite.